AB0021 Study of association of CD40-CD154 gene polymorphisms with disease susceptibility and cardiovascular risk in spanish rheumatoid arthritis patients. (23rd January 2014) - García-Bermúdez, M.; González-Juanatey, C.; Lόpez-Mejías, R.; Teruel, M.; Miranda-Filloy, J.A.; Castañeda, S.; Blanco, R.; Balsa, A.; Fernández-Gutiérrez, B.; González-Alvaro, I.; Gόmez-Vaquero, C.; Llorca, J.; et al.
Abstract : Background: Rheumatoid arthritis (RA), the prototype of inflammatory chronic diseases, is characterized by a consistent increase of cardiovascular (CV) mortality and morbidity, mainly due to an acceleration of atherosclerotic damage and multiple disease-related pathogenic mechanisms take part in this process (1-3). CD40–CD40 ligand interaction, a crucial step in autoimmune disease pathogenesis, is thought to be involved in atherogenesis and plaque rupture in RA (4). Objectives: We aimed to replicate previous findings related to RA susceptibility in Spanish population. Furthermore, as the major complication in RA disease patients is the development of CV events and elevated levels of CD40L/CD154 are present in patients with acute myocardial infarction, we assessed the potential association of the CD40 and CD154 gene variants with the CV risk in RA patients. Methods: 1505 patientsfulfilling the 1987 ACR classification criteria for RA and 1600 matched controls were genotyped for the CD40 rs1883832, rs4810485 and rs1535045, and CD154 rs3092952 and rs3092920 gene polymorphisms, using predesigned TaqMan SNP genotyping assays. Afterwards, we investigated the influence of CD40-CD154 gene variants in the development of CV events. Also, in a subgroup of patients without history of CV events, we assessed the influence of these polymorphisms in the risk of subclinical atherosclerosis. Results: Statistically significant differences in the allele frequencies for the CD40 gene promoter polymorphisms between RA patients and controls were found. However, no significant associations of these polymorphisms were observed when RA patients who suffered CV events were compared with those who did not experience CV events. Similarly, no association with subclinical atherosclerosis was found. Conclusions: CD40 SNPs promoter polymorphisms are associated with susceptibility to RA patients. However, there is no association between CV events and CD40-CD154 axis in RA. Acknowledgments: Supported by two grants from Fondo de Investigaciones Sanitarias PI06-0024 and PS09/00748 (Spain). This work was partially supported by RETICS Program, RD08/0075 (RIER) from Instituto de Salud Carlos III (ISCIII), within the VI PN de I+D+i 2008-2011 (FEDER). MGB is a recipient of a grant from Fundaciόn Española de Reumatología (FER). References: Bartoloni E, Shoenfeld Y, Gerli R. Arthritis Care Res (Hoboken). 2011;63(2):178-83. Nurmohamed MT. Autoimmun Rev. 2009;8(8):663-7. Zinger H, Sherer Y, Shoenfeld Y. Clin Rev Allergy Immunol. 2009;37(1):20-8. Montecucco F, Mach F. Rheumatology (Oxford). 2009;48(1):11-22. Disclosure of Interest: None Declared